Characteristics of austenitic stainless steel T-joints welded using the DMAG process with solid wire - Mert, Tolga; Gultekin, Nurullah; Karaaslan, Ahmet (CARL HANSER VERLAG, 2016)
X 2 CrNi 18 9 austenitic stainless steel material with web and flange thickness of 6 mm was welded by conventional GMAW and double channel shielding gas method ( DMAG) to form double fillet T-joints. The differences between these two methods were characterized by measurements of mean welding parameters, thermal camera temperature measurements, Vickers hardness profiles and bead geometries of the joints. Results show higher mean current but lower mean voltage using double channel shielding gas method. Vickers hardness differences between the two methods were insignificant. Moreover, molten mean filler metal area was larger with double channel shielding gas method, which depicted that welding speed for the same filler metal deposition could be increased and this could yield increased productivity.
Keywords: Double channel torch; stainless steel; solid wire; hardness; bead geometry; Materials Science